Malka - Pressler, Mirjam; Murdoch, Brian, 1944- (New York : Philomel Books, 2003)
In the winter of 1943, a Polish physician and her older daughter make a dangerous and arduous trek to Hungary while seven-year-old Malka, who they were forced to leave behind when she became ill, fends for herself in a ghetto
"Published in Great Britain 2002 by Young Picador. First published in 2001 in Germany by Beltz Verlag, Weinheim und Basel as Malka Mai"--T.p. verso
Keywords: Jews -- Poland -- Juvenile fiction; Holocaust, Jewish (1939-1945) -- Poland -- Juvenile fiction; Jews -- Poland -- Fiction; Holocaust, Jewish (1939-1945) -- Poland -- Fiction; Survival -- Fiction; Mothers and daughters -- Fiction; Poland -- History -- Occupation, 1939-1945 -- Fiction